2022
DOI: 10.3390/su14063259
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Based Strategies for Online Secondhand Platforms Promoting Sustainable Retailing

Abstract: Online secondhand resale platforms are a booming industry involving the growing recognition of various economic, environmental, and recreational benefits in buying and selling used items. This preliminary study explores technology-based strategies for online secondhand platforms, which contributed to the resale industry’s steady growth and digital transformation. Through a variety of literature, this study established a basis for developing research on technological innovations in online resale platforms. A mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Exploring the topic of immersive technologies to support the second-hand fashion industry from a different perspective, another study [85] found that features involving high technology, such as VR, had the least impact on users' usage of fashion resale platforms, but other digital technologies which were not immersive were more successful.…”
Section: Second-hand Refashioning Rental Owned and Recycled Fashionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploring the topic of immersive technologies to support the second-hand fashion industry from a different perspective, another study [85] found that features involving high technology, such as VR, had the least impact on users' usage of fashion resale platforms, but other digital technologies which were not immersive were more successful.…”
Section: Second-hand Refashioning Rental Owned and Recycled Fashionmentioning
confidence: 99%
“…Acceptance of circular business models and recycled products [61,71,83,85,113]; • Dematerialisation through digital fashion offerings allows consumers to have multiple new outfits for their digital channels, which reduces the need for physical items [27,65,74,[98][99][100][101][102][103][104]106,108,109,113]; • Gamification, where brands are entering existing virtual gaming worlds to encourage digital fashion purchases, or they are taking a gamification approach to their interactions with consumers [26,81,94].…”
Section: Consumer Choice or Consumptionmentioning
confidence: 99%
“…Furthermore, this paper expands the TAM and applies it to the realm of digital fashion. Now, many developed extensions of the TAM are more suitable for the information age [44,49]. However, in the current context, it still has some shortcomings due to the lack of consideration on how social and cultural factors influence users' acceptance of technology [44].…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Foreign countries started earlier in big data research than in China, and foreign research on big data pays more attention to technology and application research, which to a certain extent benefits from the strong support of the government. For example, the U.S. government has established six departments for big data research, and most of its research projects are researching big data analysis algorithms, big data storage technologies, and big data security technologies [16].…”
Section: Literature Reviewmentioning
confidence: 99%